Experiences Following Amputation among Amputees and Their Caregivers: An Exploratory Study in a Developing Country - Ohenewa, E.; Yendork, J.S.; Amponsah, B. (SAGE, 2022)
Amputation is necessitated following an accident or a medical condition often to save a patient’s life. Despite the existence of the procedure and the rising number of amputees in the Ghanaian context, the emotional experiences of both amputees and their caregivers following amputation has been largely ignored. This qualitative exploratory study explored the emotional experiences of amputees and their caregivers following amputation. Using a semi-structured interview guide, ten (10) amputees and ten (10) caregivers were interviewed. Findings revealed that caregivers and amputees experienced a built up of negative emotions following amputaion. There were slight disparities in the negative emotions experienced by amputees and their caregivers. However, for both amputees and their caregiver, the experience of gratitude and news breaking method influenced their emotional experiences. Implications of the findings are discussed.
Research Article
Keywords: negative emotions; amputation; trauma; amputees; caregivers